2014 IEEE International Conference on Advanced Networks and Telecommuncations Systems (ANTS) 2014
DOI: 10.1109/ants.2014.7057266
|View full text |Cite
|
Sign up to set email alerts
|

Novel energy model to analyze the effect of MAC and network parameters on asynchronous IEEE 802.15.4 multi-hop wireless networks lifetime

Abstract: Abstract-Design of energy efficient wireless networks is the primary research goal for evolving billion device applications like Internet of Things (IoT), smart grids and Cyber Physical Systems (CPS). Energy efficient models can reduce megawatts of power through out globe thereby reducing carbon foot print by improving overall network lifetime of large scale networks. Recent advances in physical layer have optimized energy consumption of IEEE 802.15.4 Physical layer, but energy efficiency of MAC and network la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“….56 * 10 −6 + 144.00 * 10 −6 w n−1 (1 + w) −n (28) For a packet of data, the energy used in transmitting the payload and receiving the ACK, E pack and the energy used for a CSMA E csma are relatively constant according to [48] and [49]. The variable in (22), (23) and 28is: p −1 = w n−1 (1 + w) −n . Therefore, we visualise the utility expression in (28) for 6 and 12 nodes by plotting the graph of utility against CW as shown in Fig.…”
Section: Game Utility a Utility Functionmentioning
confidence: 99%
“….56 * 10 −6 + 144.00 * 10 −6 w n−1 (1 + w) −n (28) For a packet of data, the energy used in transmitting the payload and receiving the ACK, E pack and the energy used for a CSMA E csma are relatively constant according to [48] and [49]. The variable in (22), (23) and 28is: p −1 = w n−1 (1 + w) −n . Therefore, we visualise the utility expression in (28) for 6 and 12 nodes by plotting the graph of utility against CW as shown in Fig.…”
Section: Game Utility a Utility Functionmentioning
confidence: 99%
“…Authors found their model efficient in achieving energy-efficiency; however other QoS aspects could not be addressed. Furthermore, considering applications such as IoT, Cyber Physical Systems (CPS) and smart grids Prasad et al [36] focused on state wise dynamic behaviour feature (of relay nodes) with 3-dimensional Markov MAC algorithm that achieved energy-efficient routing decision. Liu et al [37] aimed at enhancing the performance of EH-powered WSNs in three aspects: scheduling, relaying and MAC control.…”
Section: Related Workmentioning
confidence: 99%
“…Some other related literature includes [9] where cross‐layer energy optimisation has been treated. Further, the authors presented an energy model of IEEE 802.15.4 in [10], considering sensing energy, CCA energy, and active mode energy to analyse the effect of MAC and other network parameters, but the authors have not considered energy consumption for the total frame transmission.…”
Section: Introductionmentioning
confidence: 99%